Chemical in‐gel deglycosylation of O‐glycoproteins improves their staining and mass spectrometric identification. Issue 16 (8th July 2013) - Bellwied, Petra; Staubach, Simon; Hanisch, Franz‐Georg; Guttman, Andras
<x xml:space="preserve">Abstract</x> Heavily O‐glycosylated membrane‐tethered or secreted proteins often escape identification by gel‐based proteomics due to weak staining and low identification rates in MS/MS. The present protocol refers to a chemical in‐gel de‐O‐glycosylation of proteins based on repeated oxidation/elimination of glycans leaving the protein backbone intact at the gel position of the native glycoprotein. On restaining prior to spot picking, the deglycosylated proteins are detectable at increased staining intensities when applying fluorescent dyes or silver stains. Evidence shows that de‐O‐glycosylation of proteins in gels is efficient and does not introduce structural artifacts into the protein backbones. In‐gel trypsin digestion of deglycosylated proteins, such as human glycophorin A, revealed strongly enhanced sequence coverage in LC‐ESI MS/MS. The protocol is applicable in 1D and 2D gel settings within one working day.